Чого немовознавцеві бракує в загальномовному словнику - Кочерга, О. (Лексикографічний бюлетень, 2015)
Wordlists of Ukrainian dictionaries are considered in view of the needs of a nonlinguist users. Typical lacking technical adjectives are indicated, the necessity to fill in the gaps is substantiated.